Malaysia's States and Regions : From the Legal History of the Malacca Malay Empire (The Law of the Malacca Code) To the Federation of Malaya (The Federation of Malaya Agreement 1957) - Ahmad Fauzi Wan Husain, Wan; Hanie Abu Samah, Irza; Maizura Abd Rashid, Intan (International Journal of Psychosocial Rehabilitation, 2020)
The history of the state government had long begun with the people who lived in a province. The purpose of this paper is to shed light on the history of the development of state government in Malaysia. It begins with the empire of the Malacca Sultanate, which then continues its empire through generations until the formation of the Malayan state. Unfortunately, the history of the Malayan Sultanate was in the Malay version and was hard to find in English translation. This article serves as a brief explanation of the beginning of the history of the Malacca Sultanate before the formation of the Malayan Federation states. This paper hopes to give a benefit towards readers, especially historians, in understanding the Malay Federation and how these historical records contribute to world history.